2015
DOI: 10.4141/cjps-2014-339
|View full text |Cite
|
Sign up to set email alerts
|

Willows (Salix spp.) as pollen and nectar sources for sustaining fruit and berry pollinating insects

Abstract: . 2015. Willows (Salix spp.) as pollen and nectar sources for sustaining fruit and berry pollinating insects. Can. J. Plant Sci. 95: 505Á516. Willows (Salix spp.) are ubiquitous in the northern hemisphere, serving as an important pollen and nectar resource for insect pollinators and for the enhancement of insect-pollinated agricultural crops such as fruits and berries. We used a common-garden field test containing seven native North American willow species to assess attractiveness of male and female flower cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Although we haven't yet quantified flower production, anecdotal observations from ongoing pollination studies [48] show that some clones have more prolific flower production than others. Therefore, flower production for promotion of insect pollinators in various agricultural applications, such as berry or fruit production, may also be a trait for genetic selection and clonal development.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although we haven't yet quantified flower production, anecdotal observations from ongoing pollination studies [48] show that some clones have more prolific flower production than others. Therefore, flower production for promotion of insect pollinators in various agricultural applications, such as berry or fruit production, may also be a trait for genetic selection and clonal development.…”
Section: Discussionmentioning
confidence: 93%
“…Under natural conditions, INT usually occurs in direct association with stream channels, floodplains, and narrow riparian corridors. In other restoration plantings across this coal mine site, INT appeared to survive and thrive best when associated with active erosion stream channels that provided a source of water throughout most of the growing season [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high value of pollen and nectar from various Salix species in terms of reward for insects was emphasized by Ostaff et al [54] in Canada. The authors have found that Salix pollen and nectar may be highly important in early spring as a source of nutrition for pollinating insects.…”
Section: Discussionmentioning
confidence: 95%
“…Early spring emergence of flowers is extremely important in supplying nutritive rewards, such as pollen and nectar, for many native arthropods, while the host plant benefits with an increased chance of successful sexual reproduction. The most common cross-pollinators in agricultural systems are often made up of arthropods that collect pollen from many unrelated hosts such as flies belonging to the family Syrphidae, eusocial bee species such as honey bees ( Apis mellifera L.), and polylectic solitary bees (Ostaff et al 2015). Lack of discrimination among hosts allows these arthropod groups to more flexibly collect resources for survival and population growth.…”
Section: Introductionmentioning
confidence: 99%